Philip Roth. - Brauner, David (Contemporary American & Canadian Writers., 2007)
This is a groundbreaking study of the most important contemporary American novelist, Philip Roth. Reading the author alongside a number of his contemporaries, and focusing particularly on his later fiction, this book offers a highly accessible, informative and persuasive view of Roth as an intellectually adventurous and stylistically brilliant writer who constantly reinvents himself in surprising ways. At the heart of this book are a number of detailed and nuanced readings of Roth?s works both in terms of their relationships with each other and with fiction by Nathaniel Hawthorne, Thomas Pynch.